Interoperability in Systems-of-Information Systems: A Systematic Mapping Study - Fernandes, Juliana Costa; G. Neto, Valdemar V.; Santos, Rodrigo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Informationl Systems (IS) need to interoprate with other systems to provide more complex functionalities, forming largescale systems called Systems-of-Information Systems (SoIS). Interoperability is a key concern at this context. As such, solutions should be proposed to support interoperability between IS to provide products and services to (i) meet novel society demands, (ii) add value to organizations, and, at the same time, (iii) guarantee quality of those products and services. The main contribution of this paper is the externalization of factors (e.g., technical, organizational and human issues) that affect systems interoperability systems in the context of SoIS through a systematic mapping study. Results contribute to the characterization of interoperability solutions for systems, which are of great importance to identify challenges and opportunities.